SerumCovid database: Description and preliminary analysis of serological COVID-19 diagnosis in healthcare workers - Isis Didier Lins; Leonardo Streck Raupp; Caio Bezerra Souto Maior; Felipe Cavalcanti de Barros Felipe; Márcio José das Chagas Moura; João Mateus Marques de Santana; Alexsandro dos Santos; Marcelo Victor de Arruda Freitas; Ramon Nascimento Silva; Ewerton Henrique da Conceição; José Cândido Ferraz; Alice Araújo; et al. (PLoS ONE, 2022)
Serological databases represent an important source of information to perceive COVID-19 impact on health professionals involved in combating the disease. This paper describes SerumCovid, a COVID-19 serological database focused on the diagnosis of health professionals, providing a preliminary analysis to contribute to the understanding of the antibody response to the SARS-CoV-2. The study population comprises 321 samples from 236 healthcare and frontline workers fighting COVID-19 in Vitória de Santo Antão, Brazil. Samples were collected from at least six days of symptoms to more than 100 days. The used immunoenzymatic assays were Euroimmun Anti-SARS-CoV-2 ELISA IgG and IgA. The most common gender in SerumCovid is female, while the most common age group is between 30 and 39 years old. However, no statistical differences were observed in either genders or age categories. The most reported symptoms were fatigue, headaches, and myalgia. Still, some subjects presented positive results for IgA after 130 days. Based on a temporal analysis, we have not identified general patterns as subjects presented high and low values of IgA and IgG with different evolution trends. Unexpectedly, for subjects with both serological tests, the outcome of IgA and IgG tests were the same (either positive or negative) for more than 80% of the samples. Therefore, SerumCovid helps better understand how COVID-19 affected healthcare and frontline workers, which increases knowledge about the infection and enables direct prevention actions.